Religion and society : an agenda for the 21st century - Haar, Gerrie ter.; Tsuruoka, Yoshio, 1952- (International Studies in Religion and Society, 2007)
Religion is set to be a major force in the twenty-first century. Here is a book that tells us what the world's leading scholars have to say about this. Issues of conflict and peace, ethical questions concerning the use of advanced technology, explanations of the global religious revival, and the role of women in religious leadership, as well as questions about how to study religion, are all discussed. It is a volume that ranges exceptionally widely, in terms of the themes discussed, the variety of disciplines, and the participation of international scholars debating with each other. One section of the book is devoted to Japanese scholarship concerning the world's major religions. Contributors include: Talal Asad, Chin Hong Chung, Armin Geertz, Gerrie ter Haar, Rosalind Hackett, Eiko Hanaoka, Shōtō Hase, Mark Juergensmeyer, Noriko Kawahashi, Kiyotaka Kimura, Ursula King, Pratap Kumar, William Lafleur, Sylvia Marcos, Tomoko Masuzawa, Ebrahim Moosa, Kōjirō Nakamura, Vasudha Narayanan, Haruko Okano, Suwanna Satha-Anand, Susumu Shimazono, Noriyoshi Tamaru, Masakazu Tanaka, Hiroshi Tsuchiya, Yoshio Tsuruoka, Manabu Watanabe, Pablo Wright.